Eurasian Economic Perspectives Proceedings of the 20th Eurasia Business and Economics Society Conference - Vol. 2 (Eurasian Studies in Business and Economics,, 2018)
This volume presents selected papers on recent management research from the 20th Eurasia Business and Economics Society (EBES) Conference, which was held in Vienna in 2016. Its primary goal is to showcase advances in the fields of public economics, regional studies, economic development and inequality, and economic policy-making. Reflecting the contemporary political climate, many of the articles address the effectiveness, relevance and impact of European Union policies. In addition, the volume features empirical research from less-researched countries such as Kazakhstan, the Republic of Macedonia, Belarus, and Lithuania, among others. .